A Decade of Surgical Management of Renal Cell Carcinoma with IVC Thrombus and Bilateral Renal Tumors: Emphasis on Auto-transplantation (Journal of Kidney Cancer, 2025)
To assess the surgical outcomes and techniques in managing renal cell carcinoma (RCC) with inferior vena cava (IVC) thrombus and bilateral renal tumors with a focus on the role of autotransplantation in complex cases, this retrospective study analyzed 58 patients treated at our center between 2013 and 2023 for RCC with tumor thrombus extending into the IVC and, in some cases, the right atrium (RA). Surgical management included radical nephrectomy and thrombectomy with techniques adapted to thrombus level. For level I and II thrombi, innovative occluding maneuvers were used to control the contralateral renal vein. For level IV thrombi, a beating heart technique combined with cardiopulmonary bypass (CPB) was employed. Of the 10 patients with bilateral renal tumors, 2 underwent autotransplantation and 8 underwent bilateral partial nephrectomy. In this 10-year retrospective study of 58 patients with either RCC with venous tumor extension or bilateral RCC, 40 males and 18 females, with a mean age of 66 ± 8 years. Tumor involvement was predominantly right-sided (72.4%). Thrombus levels included 53.44% Level I, 25.9% Level II, and 3.4% Level IV. Intraoperative and postoperative complications were minimal, affecting 10 patients; patients with Level I thrombus had a better survival rate; and one patient with Level IV thrombus died postoperatively. The mean blood loss was 360 mL and the mean operative time was 195 minutes. Histopathology revealed clear cell carcinoma in 65.5% of cases. Among the 10 patients with bilateral renal tumors, autotransplantation and partial nephrectomies resulted in excellent renal preservation and favorable outcomes. This study demonstrates the effectiveness of radical nephrectomy and thrombectomy for RCC with venous tumor extension. Tailored surgical techniques, including autotransplantation for bilateral tumors, resulted in excellent outcomes with minimal complications. Personalized surgical strategies were key to preserving renal function and improving survival in complex RCC cases.